OCEAN SUSTAINABILITY MOVEMENT MELALUI PENANAMAN MANGROVE DI JEMBATAN PELANGI DESA LONTAR - Mohammad Shobri; Rudy Pramono; Jessica Elfani Bermuli; Junius Hardy; Hady Soenarjo; Dinda Sekar Syallomitha (Jurnal Sinergitas PKM & CSR, 2025)
Indonesia, as an archipelagic nation with the world's longest coastline, possesses vast marine ecosystems, including mangrove forests. Unfortunately, mangrove degradation continues to increase due to human activities and low environmental awareness, including in the Rainbow Bridge area of Lontar Village. This region is prone to tidal floods and abrasion due to sparse mangrove cover and rising sea levels. In response, the Environmental Conservation Department of the Service Learning Community (SLC) of Pelita Harapan University organized the Ocean Sustainability Movement (OSMO) 2025 program as a tangible contribution to coastal conservation. The main objectives were to plant mangrove seedlings to support marine ecosystem stability and to provide education through seminars and technical training to volunteers. The program also aimed to foster environmental awareness among students through active involvement in conservation actions. The results showed that 95% (1,425 seedlings) of the planting target was achieved, 85% of volunteers demonstrated increased knowledge and planting skills, and 85% expressed high satisfaction and interest in participating in similar future programs.